Degradation of piezoelectric device as an energy harvester under equivalent traffic stress condition. (17th February 2019) - Pole, Mayur; Gamboa, Bryan; Bhalla, Amar; Guo, Ruyan
Abstract: Piezoelectric materials have widely been used for applications in microelectromechanical systems, electromechanical devices, civil infrastructure, in transportation and smart devices. The performance of these devices is largely affected by their loading and unloading history when used in electromechanical applications. Lead Zirconium Titanate (PZT), a specific material of piezoelectric ceramics, which upon repetitive cyclic compressive load undergoes both electrical and mechanical degradation over a period of time and number of cycles. The degradation of piezoelectric properties with the application of cyclic compressive loading and the mechanical fatigue behavior were investigated on PZT-5H.